2011
DOI: 10.5005/jp-journals-10005-1088
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy and its Implications in Dentistry

Abstract: Background The concept of transferring genes to tissues for clinical applications has been discussed for nearly half a century. The exponential increase in our ability to manipulate the genetic material of a cell via recombinant DNA technology has brought this goal closer to realization. The original perception that gene therapy should be considered only for a few major organs as a means of treating life-threatening disorders that are refractory to conventional treatment has changed. There are many non-life-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The transfer of BSP gene by gene therapy procedures to an osseous defect is known to regenerate alveolar bone. 4 Various studies have shown the positive role of BSP gene in regenerating alveolar bone around teeth and implantsupported prosthesis. The DNA vaccines have also been tried in the field of dentistry, particularly for preventing periodontal conditions and dental caries.…”
Section: Applications In Dentistrymentioning
confidence: 99%
See 4 more Smart Citations
“…The transfer of BSP gene by gene therapy procedures to an osseous defect is known to regenerate alveolar bone. 4 Various studies have shown the positive role of BSP gene in regenerating alveolar bone around teeth and implantsupported prosthesis. The DNA vaccines have also been tried in the field of dentistry, particularly for preventing periodontal conditions and dental caries.…”
Section: Applications In Dentistrymentioning
confidence: 99%
“…The technique will result in production of clusters of cells with a specifically designed genetic make-up as necessary. 1,3,4 Alternatively, if the patient's somatic cells have been removed from the body, they can be exposed to the vector in the laboratory. The cells with the desired vectors with attached DNA fragments are reintroduced into the patient-specific tissue.…”
Section: General Principles Of Gene Transfermentioning
confidence: 99%
See 3 more Smart Citations